Anatomy and physiology for the health professions - Bautista, Joy N. (Manila, Philippines : Educational Publishing House, 2006)
The healthcare profession of today is very much unlike the profession that it was not so long ago. With advancing technologies at an ever-frightening pace and the accumulation of new knowledge at a snap of a finger, the present day healthcare profession is indeed a very exciting, and challenging, one.- - Preface.
Chapter 1. Understanding the human body -- Chapter 2. Chemistry of life -- Chapter 3. Cells -- Chapter 4. Tissues and membranes -- Chapter 5. The integumentary system -- Chapter 6. The skeletal system -- Chapter 7. The muscular system -- Chapter 8. The nervous system -- Chapter 9. The senses -- Chapter 10. The endocrine system -- Chapter 11. The heart -- Chapter 12. The blood and blood vessels -- Chapter 13. The lymphatic system -- Chapter 14. The respiratory system -- Chapter 15. The digestive system -- Chapter 16. The urinary system -- Chapter 17. The human reproductive system.
Includes bibliographical references.
Keywords: HUMAN ANATOMY; HUMAN PHYSIOLOGY